Atypical presentations of MERS-CoV infection in immunocompromised hosts. Issue 11 (November 2017) - Kim, Si-Ho; Ko, Jae-Hoon; Park, Ga Eun; Cho, Sun Young; Ha, Young Eun; Kang, Ji-Man; Kim, Yae-Jean; Huh, Hee Jae; Ki, Chang-Seok; Jeong, Byeong-Ho; Park, Jinkyeong; Jang, Jun Ho; et al.
Abstract: During the 2015 Korean MERS outbreak, we experienced atypical presentations of MERS-CoV infections in three immunocompromised hosts that warranted exceptional management. Case 1 showed delayed symptom development after a four-day asymptomatic period, Case 2 experienced a 20-day incubation period, and Case 3 exhibited persistent viral shedding without clinical deterioration. Recognizing these exceptions is extremely important in the management of MERS-CoV-exposed or -infected patients and for control of potential MERS outbreaks.